2002
DOI: 10.1007/bf03165081
|View full text |Cite
|
Sign up to set email alerts
|

Chronic graft-versus-host disease and late effects after hematopoietic stem cell transplantation

Abstract: Late effects following HSCT are related to either the transplant process or to the transplant preparative regimen. Problems related to the transplant process include delayed recovery of the immune system and chronic GVHD. Chronic GVHD presents between 3-14 months post-HSCT in approximately 20% of matched sibling transplants and 40% of matched unrelated donor recipients. Most commonly involved sites are skin, mouth, liver, gastrointestinal tract, and eye. Patients with platelet count < 100,000/ml and receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 94 publications
0
31
0
Order By: Relevance
“…[1][2][3] However, recovery after transplantation is prolonged, often because of complications such as chronic GVHD, cardiopulmonary compromise, endocrinopathies, musculoskeletal disorders, and subsequent malignancies. [4][5][6][7][8][9][10][11][12][13][14][15][16] Recently, we have demonstrated that the cumulative incidence of severe or life-threatening chronic health conditions approaching 35% at 10 years after HCT. 17 These complications contribute significantly to the late morbidity and mortality experienced by HCT survivors, 2,3,17 with a potential impact on their psychological health.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, recovery after transplantation is prolonged, often because of complications such as chronic GVHD, cardiopulmonary compromise, endocrinopathies, musculoskeletal disorders, and subsequent malignancies. [4][5][6][7][8][9][10][11][12][13][14][15][16] Recently, we have demonstrated that the cumulative incidence of severe or life-threatening chronic health conditions approaching 35% at 10 years after HCT. 17 These complications contribute significantly to the late morbidity and mortality experienced by HCT survivors, 2,3,17 with a potential impact on their psychological health.…”
Section: Introductionmentioning
confidence: 99%
“…In the acute phase, there are four stages of severity: hyperemia, chemosis, pseudomembranous conjunctivitis with complete loss of conjunctival epithelium and finally, compromise of the www.intechopen.com corneal epithelium. (Jabs et al, 1989;Sanders, 2002;Uchino et al, 2006) Its presence is related to vital prognosis with a mortality rate of 90% for stages 2 through 4 (Coskuncan 1994, Ohkoshi 1992. Fig.…”
Section: Orbit and Eyelidsmentioning
confidence: 99%
“…Supplementation of the active metabolites 1.25(OH) 2 D 3 or 25(OH) 3 could result in a superior effect on bone density and contribute to modulation of GVHD. 54,55 Vitamin B 12 . Regarding water-soluble vitamins, only vitamin B 12 has been discussed in the literature.…”
Section: Nutritional Support In Gvhd Of the Digestive Tract Bs Van Dementioning
confidence: 99%